Pengembangan Media Pembelajaran Komik pada Materi Menganalisis Struktur Teks Biografi Kelas X SMK Negeri 1 Lotu - Arman Suka Damai Zega; Riana; Lestari Waruwu (Indo-MathEdu Intellectuals Journal, 2023)
The purpose of this research is to develop comic learning media on the material of analyzing the structure of biography text in class X SMK Negeri 1 Lotu which is valid/worthy, practical, and effective. This type of research is research and development (Research and Development). The development model used is the 4D model which consists of four stages, namely the Define stage, Design stage, develop stage, and Disseminate stage. Comic learning media developed through the validity test stage by three validators (material and content experts, linguists, and design experts), small group tests and field tests conducted in class X DPIB SMK Negeri 1 Lotu. Based on the results of research conducted by three validators/experts, comic learning media has been tested valid and feasible by 100% material and content expert validators, 100% language expert validators, and 96% design expert validators. The practicality of comic learning media in the small group test was 93%, and the field test was 94% with very practical criteria. The effectiveness of comic learning media has also been tested very effective with the percentage of classical completeness in the small group test of 100%, and the field test of 87.5%.